-TRANSITIVE DIGRAPHS PRESERVING A CARTESIAN DECOMPOSITION. (31st March 2015) - MORRIS, JOY; SPIGA, PABLO
Abstract : In this paper, we combine group-theoretic and combinatorial techniques to study -transitive digraphs admitting a cartesian decomposition of their vertex set. In particular, our approach uncovers a new family of digraphs that may be of considerable interest.